Effect of Na, Mg, Ca chloride salts on mineral element, proline and total protein contents in rice (Oryza sativa L.) grown in vitro - Pınar Orcan; Mehmet Yusuf Orcan (International Journal of Secondary Metabolite)
In this study, the effects of different types and concentrations of salts on local Siverek rice plant (Oryza sativa L.) grown in vitro were investigated in terms of mineral elements (K, Ca, P, Mg, Na, Fe, Cu, Zn, Mn, Mo, Co), proline, and total protein content. Sterilized seeds were planted in hormone-free and salt-free MS medium. After one week, the seedlings were subjected to different concentrations of NaCl, CaCl2, and MgCl2 salts (0, 30 mM, 90 mM) in order to evaluate the effect of salinity on plant growth and development. In response to salt stress, a decrease in nutrient elements was observed for all three types of salt compared to the control group, which can be attributed to disruptions in ion balance. Changes in element levels generally showed varying levels of increase or decrease depending on both the type and concentration of the salt and these changes were statistically significant. The increase in proline level was found to be directly proportional to the changes in the amounts of Ca, Mg, K, and Na elements. Both total protein and proline content showed the lowest values for all salt concentrations with CaCl2, while the highest values were obtained with NaCl. In conclusion, the changes in the level of mineral elements, total protein, and proline content levels, which decrease or increase in different ratios, depending on the type and concentration rising of the salt, are associated with the varying tolerance of the plant to different types of salts.